Schlaganfall und epileptische Anfälle: Aktuelle Behandlung und Zukunftsperspektiven - Stefan, Hermann (Zeitschrift für Epileptologie, 2021)
Epileptic seizures can complicate the treatment of stroke and influence the prognosis. Poststroke seizures and epilepsy require individual indications and selection of treatment including a benefit-risk assessment of efficacy and possible side effects of antiictal drugs. Nowadays, after individual consideration of the indications the occurrence of an epileptic seizure does not represent a contraindication for i.v. thrombolysis or thrombectomy. In addition to trial experiences with antiictal drugs used for seizures after stroke, new approaches for possible primary prevention with antiepileptic drugs are discussed.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Anticonvulsant; Biomarker; Interactions; Prognosis; Thrombolysis